KEWENANGAN PEMERINTAH PUSAT DAN PEMERINTAH DAERAH DALAM PENANGANAN PANDEMI COVID-19 - Agung Jospriady (2021)
The determination of the Covid-19 as a National Disaster through Presidential Decree Nomor 12 of 2020 is the response of the global pandemic set by the World Health Organization. Indonesia as a Unitary State based on Regional Autonomy, has its own challenges in handling this global pandemic. The division of the Authority of the Regional and the Central Government becomes the discourse of the community. Some local governments take policies in handling in their regions. These policies are often inconsistent with the command of the Central Government. For the sake of creating a good handling of the global pandemic, the Regional and Central Government must synergize. This study provides an overview of regional autonomy in handling the Covid-19 pandemic. The research identifies that the authority between the central and regional governments is important for the creation of a harmonious relationship.